Work Fatigue Profiles: Nature, Implications, and Associations With Psychological Empowerment - Blais, Ann-Renée; Gillet, Nicolas; Houle, Simon A.; Comeau, Caitlin A.; Morin, Alexandre J. S. (Frontiers in Psychology, 2020)
The present study examined the distinct configurations, or profiles, taken by work fatigue dimensions among samples of military (n = 1,436) and civilian (n = 2,477) employees. We also tested profile similarity across these two samples of employees. In addition, this research documented the relations between the identified work fatigue profiles, one predictor variable (psychological empowerment), and a series of attitudinal outcomes (job satisfaction, career satisfaction, and turnover intentions) among military employees. Six profiles of employees characterized by different levels of global and specific (emotional, physical, and mental) work fatigue were identified using latent profile analyses: Low Fatigue, Physically and Emotionally Depleted, Emotionally Depleted, Globally and Mentally Depleted, Globally and Emotionally Depleted, and Balanced. In both samples, employees corresponding to the Balanced profile displayed average levels of global and specific work fatigue. However, this profile slightly differed across sample, as indicated by the observation of work fatigue levels that were slightly higher among the military than among civilians. Militaries’ perceptions of psychological empowerment were significantly related to their likelihood of belonging to all profiles. In turn, militaries’ career satisfaction, job satisfaction, and turnover intentions were also found to differ as a function of profile membership.